A case report of short-chain acyl-CoA dehydrogenase deficiency (SCADD) - Lampret, Barbka Repic (Biochem Med (Zagreb), 2015)
BACKGROUND: Short-chain acyl-CoA dehydrogenase deficiency (SCADD) is a rare inherited mitochondrial fatty acid oxidation disorder associated with variations in the ACADS (Acyl-CoA dehydrogenase, C-2 to C-3 short chain) gene. SCADD has highly variable biochemical, genetic and clinical characteristics. Phenotypes vary from fatal metabolic decompensation to asymptomatic individuals. SUBJECT AND METHODS: A Romani boy presented at 3 days after birth with hypoglycaemia, hypotonia and respiratory pauses with brief generalized seizures. Afterwards the failure to thrive and developmental delay were present. Organic acids analysis with gas chromatography-mass spectrometry (GS/MS) in urine and acylcarnitines analysis with liquid chromatography-tandem mass spectrometry (LC-MS/MS) in dried blood spot were measured. Deoxyribonucleic acid (DNA) was isolated from blood and polymerase chain reactions (PCRs) were performed for all exons. Sequence analysis of all exons and flanking intron sequences of ACADS gene was performed. RESULTS: Organic acids analysis revealed increased concentration of ethylmalonic acid. Acylcarnitines analysis showed increase of butyrylcarnitine, C4-carnitine. C4-carnitine was 3.5 times above the reference range (<0.68 µmol/L). Confirmation analysis for organic acids and acylcarnitine profile was performed on the second independent sample and showed the same pattern of increased metabolites. Sequence analysis revealed 3-bp deletion at position 310-312 in homozygous state (c.310_312delGAG). Mutation was previously described as pathogenic in heterozygous state, while it is in homozygous state in our patient. CONCLUSIONS: In our case clinical features of a patient, biochemical parameters and genetic data were consistent and showed definitely SCAD deficiency.